A cache coherence scheme for developing mobile cooperative applications. (2017) - Berkenbrock, Carla Diacui Medeiros; Berkenbrock, Gian Ricardo; Hirata, Celso
The advance of mobile computing and network technology allows the integration of mobile devices for cooperative applications. The available techniques for developing cooperative applications were elaborated mainly to strongly coupled environments where disconnection is not an issue. The development of synchronous cooperative applications presents challenges since disconnection can disrupt the collaborative work and frustrate users' expectations. There are cache coherence schemes for maintaining data coherence that provide a reasonable performance of wireless applications with mobile devices; however, those schemes do not consider the requirements of processing and communication of synchronous cooperative systems. In this paper we propose a cache coherence scheme for the development of mobile synchronous cooperative work applications that is based on periodic notifications of updates and provides aspects of awareness information. The evaluation of the proposed scheme was conducted through controlled experiments. For the experiments, a case study involving a cooperative game application was developed. The results indicate that the scheme ensures cache coherence, concurrency control and provides awareness information for mobile cooperative work.